The larva of Alpopsyche ucenorum (McLachlan 1876) (Trichoptera: Limnephilidae) with notes on its systematic position and ecology - Waringer, Johann; Botosaneanu, Lazare; Le Guellec, Gwenole (Zootaxa, 2011)
The paper gives a description of the hitherto unknown larva of Alpopsyche ucenorum (McLachlan 1876). Information on the morphology of this larva is given and the most important diagnostic features are illustrated. In the context of already available keys, the larva of Alpopsyche keys together with Allogamus uncatus (Brauer). The 2 species may be separated by the larger head width of A. uncatus and the position for the beginning of the lateral fringe (A. ucenorum: 3rd abdominal segment, A. uncatus: 2nd segment). With respect to zoogeography, A. uncatus is widely distributed in Europe whereas A. ucenorum is restricted to the western Alps. In addition, ecological facts are summarized and the systematic position within Limnephilidae is discussed.